O processo educativo da formação de um grupo de trabalho de mobilização social no caso do zoneamento de Mato Grosso - Amorim, Denize Aparecida Rodrigues de (2011)
This research in Environmental Education presents as object of study the Social Mobilization Work Group (GTMS), created on August 19th 2008 by active militants that participate of nets, groups, movements and socio-environmental entities in Mato Grosso during the conflicts included in the public hearings carried out by the Legislative Assembly of Mato Grosso, in the debate of the Policy of Land Management and its main instrument – the Ecological Socioeconomic Zoning (ZSEE). This research aimed at understanding how the popular participation constructs public policies in a dynamic and organizational way, in political actions of Environmental Education, noticed under the point of view of the participant subjects. These, through meetings, created the GTMS, acting in the proposition and defense of a participative project of ZSEE, in Mato Grosso, and carried out in the period of 2008-2011. The methodology used was that of the participant research, raising issues along with the GTM Environmental Education and public policies. The reflections were materialized in pedagogical participative tactics, constructed during the process of discussion for the elaboration of ZSEE law. These tactics must be understood in the light of a learning community that learned to participate during the trajectory, taking advantages of the “gaps” of the representative democracy to make itself heard and to resist as a movement that transforms politics into a militancy. The strength that comes from this militancy can be classified as from “movement”, “rational”, “heart”, “community” among others in which the social movements found motivation for the debate of a public policy. After more than three years in which there were exchanges of knowledge, responsibilities, experiences and invention of pedagogical participative tactics, the GTMS reflected about its way of participation and militancy, which translate the values of an educative process that give the concrete form of an ecology of resistance, a conception based on epistemology, axiology and praxiology of the Environmental Education carried out by the social movements in Mato Grosso.